Targeted Nanomaterials: Overcoming Instability of Antibody‐Nanomaterial Conjugates: Next Generation Targeted Nanomedicines Using Bispecific Antibodies (Adv. Healthcare Mater. 16/2016). Issue 16 (24th August 2016) - Howard, Christopher B.; Fletcher, Nicholas; Houston, Zachary H.; Fuchs, Adrian V.; Boase, Nathan R. B.; Simpson, Joshua D.; Raftery, Lyndon J.; Ruder, Tim; Jones, Martina L.; de Bakker, Christopher J.; Mahler, Stephen M.; Thurecht, Kristofer J.
Abstract : Christopher B. Howard, and co‐workers report the generation of targeted nanomaterials for cancer theranostics by mixing of hyperbranched polyethylene glycol polymers with bispecific antibodies (BsAbs) on page 2055. The cover represents a facile method to generate actively targeted nanomaterials using polymeric nanomaterials, coupled to a BsAb with dual specificity for polymer and cancer targets such as Epidermal Growth Factor Receptor. The image captures effective tethering of the BsAb (yellow‐red) to polymeric nanomaterials (blue), creating a bio‐nanomaterial that targets cancer cells. Cover design by Sumukh Kumble .